Postmodern Exploration of Conspiracy Theories and Memory Manipulation in James Dashner's The Maze Runner - HOUARI ,Wafa; Kourdourli, Abdelkader (Faculty of Letters and Foreign Languages Department of English, 2024)
In The Maze Runner, James Dashner takes readers into a dystopian world where a group of teenagers, known as the Gladers, who have lost their memories, face the tough task of finding their way through a dangerous maze. The novel looks at important themes like memory and identity, highlighting the psychological and philosophical challenges that arise in harsh environments. This study examines how the connection between memory and identity helps to understand social and psychological issues, especially through John Locke’s theory that memory is key to who we are. Additionally, the analysis explores how the conspiracy theories created by the organization known as the World In Catastrophe: Killzone Experiment Department (WICKED) shape the Gladers' understanding of their situation and their sense of self. By applying the descriptive analytical method, the research focuses on significant moments, character development, and symbols in the text. By providing detailed descriptions and analyses, this study shows how Dashner’s portrayal of memory manipulation and identity formation reflects deeper psychological and social issues. Ultimately, the findings highlight the novel's importance in discussions about identity, memory, and the psychological effects of living in a controlled environment.